Study on content-audience alignment: Instagram influencers' engagement strategies - Haris Herdiansyah; Maskan, Olivina (Faculty of Communications Science, Dr. Soetomo University, 2025)
Abstract In the era of digital communications, social media influencers significantly shape consumer behaviour and engagement. This study investigated the impact of an influencer’s role as an opinion leader and the perceived information quality on Instagram audience engagement intentions, mediated by perceived fit with personal interests. Engagement intentions were operationalised through respondents' willingness to follow the influencer’s advice, interact with content, and recommend the influencer to others. Data were collected via a structured online survey based on a sample of 500 followers of an educational influencer. Path analysis using SPSS revealed that opinion leadership and information quality significantly enhanced engagement intentions, which amplified these effects when mediated by perceived influencer-audience alignment. This study builds upon existing literature, such as the two-step flow model, perceived quality of information, and self-congruity, by addressing gaps in their application and relevance to the dynamic environment of social media influencer marketing. While limited to a single educational influencer, the findings offer insights for influencers and marketers to showcase credibility, deliver quality content, and align with audience interests to improve engagement. Future research should expand to include diverse influencers and audience demographics across multiple platforms to enhance the generalisability and applicability of findings.